Metoda door-to-door i jej zastosowanie przez lubelskich radnych w trakcie kampanii wyborczej do Rady Miasta w 2010 r. - Łukasik-Turecka, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The paper concerns door-to-door canvassing and its use by Lublin councilors during the 2010 election campaign for the City Council. The results of the survey presented in the text show to what extent the method was applied by the winners in the elections. In February 2011 the author approached the councilors via the President of the Lublin City Council asking them to fill in a questionnaire on door-to-door canvassing. Twenty out of thirty one councilors returned the questionnaires, accounting for 64.5% of all the respondents. These questionnaires provided the research material for analysis.